EDUKASI PEMANFAATAN TANAMAN OBAT KELUARGA BAGI SISWA SEKOLAH DASAR - Nur Rahmawati, Aulia; Firdaus, Dzaki Fikri; Kurniaaji, Bayu; Rachmawati, Anggita; Prastika, Cahya Harum; Mulyani, Indah Tri (Gapenas Publisher, 2025)
Family Medicinal Plants (TOGA) are plants that can be cultivated in the yard and used for traditional medicine, as a eradication, prevention and self-treatment. Knowledge related to TOGA needs to be trained as early as possible to support National Drug Security. Therefore, early education is necessary to instill awareness and understanding of the importance of TOGA in everyday life. The situation that occurred at SDN Alasombo 3 is that SDN Alasombo 3 must take a local content of Agriculture, but knowledge related to medicinal plants (TOGA) is still not taught. Through Community Service (PkM) activities, the team can contribute to improving health literacy of elementary school students through educational and participatory methods. PkM activities are carried out by providing education related to TOGA, providing assistance related to TOGA planting in the schoolyard, and handing over TOGA posters to be displayed in each classroom. PkM activities provide increased student knowledge based on pretest and posttest results with statistically significant results (p = 0.0034 < 0.005). The activity also received a response of